(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The present study emerges from the need to study the factors that influenced the conformation of the role and media representation of the new or modern first ladies in Chile, especially Rosa Markmann -who held the position between 1946 and 1952-. In this investigation, the trans-Andean Eva Perón (Argentine first lady between 1945 and 1952) emerges as a key figure. Although Rosa and Evita did not know each other personally, we believe that the flow of press and ideas between the two countries may have influenced, or at least encouraged in some way, the Chilean first lady becoming a pioneer in terms of new characteristics that he gave to the role. In this paper we analyze three examples that aim to illustrate the idea raised as they reflect coincidences in their actions, however in all three cases, Eva was a pioneer and had great media coverage: in the field of social assistance, the two changed the traditional role of the first ladies in their respective countries, taking a step from charity towards a broad and organized social action policy; in the political field they coincided in their struggle to obtain the feminine vote; and in the field of international relations, they made trips abroad that were not without controversy and that reflect the global political tensions of the moment. Finally, we conclude that to study the role, its characteristics and mutations, not only should a look be taken at national factors, but it is always important to look at possible foreign influences since countries are and have always been part of the political, economic and world culture.